Severe aortic stenosis in octogenarian: is surgical aortic valve replacement a good option?. (26th April 2021) - Menezes Fernandes, R; Costa, HA; Bispo, JS; Mota, TF; Bento, D; Marques, N; Jesus, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Aortic stenosis (AS) is the most prevalent valvular heart disease among the elderly, reaching 8, 1% in 85 years-old patients. Symptomatic severe AS entails a high risk of morbidity and mortality without valve replacement, and increasing age is associated with higher surgical risk. Purpose: To determine the prognostic impact of advanced age in patients with severe AS referred to surgical valve replacement. Methods: We conducted a retrospective study encompassing patients referred to surgical aortic valve replacement due to severe AS, from January 2016 to December 2018. Clinical characteristics, diagnostic studies and follow-up were analysed. Patients were divided in two groups according to the age: <80 and ≥80 years old. Independent predictors of mortality and/or re-hospitalization were identified through a binary logistic regression analysis, considering p = 0, 05. Results: A total of 222 patients were included, with a 64, 4% male predominance and a median age of 75 years old. 27, 5% had concomitant surgical coronary artery disease and 87, 4% waited in an out-patient setting. Median delay until surgery was 87 days and median follow-up after surgical referral was 517 days. 59 patients (26, 8%) had ≥ 80 years old. Male gender (69, 6% vs 50, 8%; p = 0, 01), smoking habits (14, 3% vs 1, 7%; p = 0, 024), higher glomerular filtration rate (75, 5 vs 63, 2 ml/min; p = 0, 001) and lower Euroscore II values (2, 89% vs 4, 64%; p = 0, 003) were more common in younger patients. Global mortality rate (27, 1% vs 15, 5%; p = 0, 05) and the composite of mortality or re-hospitalization (52, 5% vs 36, 6%; p = 0, 034) were more frequent in older patients. Despite re-hospitalizations were also more common (37, 3% vs 29, 2%), they did not reach statistical significance (p = 0, 252). After multivariate analysis, advanced age was not an independent predictor of mortality and/or re-hospitalization. In this population, only the presence of extracardiac arteriopathy (p = 0, 007; p = 0, 006) and pulmonary hypertension (p = 0, 004; p = 0, 002) were both independent predictors of mortality and the composite of mortality or re-hospitalization. Conclusion: Older patients with AS have higher mortality, but advanced age was not an independent predictor of mortality and/or re-hospitalization. The decision to perform aortic valve replacement should be discussed in the Heart Team, considering patient's comorbidities and performing a comprehensive geriatric evaluation, not just focusing on age itself.